Implementation of Coordinated Auto-Pairing Design in Wireless Sensor Networks Using Gateway-to-Node Handshake Method - Dzulfikar; Rosyid, Nur Rohman; Adrian, Ronald; Amalyris, Waffiyah; Subardono, Alif (Emitor: Jurnal Teknik Elektro, 2024)
In the current and future era of automation, the widespread utilization of Wireless Sensor Network (WSN) technology becomes essential. The ease of installation, configuration, and management of WSN system devices involving sensor nodes is a crucial factor in the effective utilization of this system. The way sensor nodes connect to the gateway/controller in a large and widespread WSN system is a pivotal point. The experimentation in this research has successfully developed a coordinated auto-pairing protocol between the controller/gateway and sensor nodes using a handshake method approach. The results of the coordinated auto-pairing process between the controller and nodes indicate an average time of 435ms per node and a data transmission accuracy of 97%.